Seroprevalences of antibodies to Neospora caninum and Toxoplasma gondii in zoo animals - Sedlák, K; Bártová, E (Veterinary parasitology, 2006)
Neospora caninum is an apicomplexan parasite that causes neuromuscular disease in dogs and abortions in cattle. Little is known about the prevalence of antibodies to this parasite in zoo animals. Sera from 556 animals, from 13 Czech and Slovak zoos were tested for antibodies to N. caninum and Toxoplasma gondii by indirect fluorescent antibody test. Antibodies to N. caninum were found in 31 of 556 zoo animals (5.6%), representing 18 of 114 species tested: Eurasian wolf (Canis lupus lupus), Maned wolf (Chrysocyon brachyurus), fennec (Vulpes zerda), cheetah (Acinonyx jubatus), jaguarundi (Herpailurus yaguarondi), Eurasian lynx (Lynx lynx), Indian lion (Panthera leo goojratensis), fisher (Martes pennanti), blackbuck (Antilope cervicapra), European bison (Bison bonasus), lechwe (Kobus leche), African buffalo (Syncerus caffer caffer), eland (Taurotragus oryx), sitatunga (Tragelaphus spekei gratus), Thorold's deer (Cervus albirostris), Eastern elk (C. elaphus canadensis), Vietnam sika deer (C. nippon pseudaxis) and Père David's deer (Elaphurus davidianus). Titres ranged from 1:40 to 1:2560. The highest prevalence 50% was found in family mustelidae of the order carnivora. Antibodies to T. gondii were detected in 193 of 556 zoo animals (34.7%) representing 72 of 114 species tested, with titres ranging from 1:40 to 1:40960. The highest prevalence 100% was found in families: hyaenidae, mustelidae, ursidae and viveridae of the order carnivora. The results of this study indicate that zoo animals have more exposure to T. gondii than to N. caninum. It is the first report of seroprevalence of antibodies to N. caninum in European zoo animals.
Keywords: Animals; fluorescenční protilátková technika nepřímá; Slovakia; Toxoplasma; kokcidióza; Coccidiosis; toxoplazmóza zvířat; séroepidemiologické studie; protilátky protozoální; Antibodies, Protozoan; Czech Republic; Seroepidemiologic Studies; Česká republika; Toxoplasmosis, Animal; zvířata v ZOO; Slovenská republika; Neospora; zvířata; Fluorescent Antibody Technique, Indirect; Animals, Zoo